The Probe Team [episode no. 311] (Probe Productions, 1994)
A lost cause is about comfort women appealing for renumeration of theur sufferings to the visiting Japanese Prime Minister Muruyama. Operation Siraniko is the exposition of car pseudo-mechanics operation. Intimately, Julia is about the British singer/songwriter, Julia Fordham.